Ramadan diurnal intermittent fasting modulates SOD2, TFAM, Nrf2, and sirtuins (SIRT1, SIRT3) gene expressions in subjects with overweight and obesity - Madkour, Mohamed I.; T. El-Serafi, Ahmed; Jahrami, Haitham A.; Sherif, Naglaa M.; Hassan, Rasha E.; Awadallah, Samir; Faris, “Mo'ez Al-Islam” E. (Diabetes research and clinical practice, 2019)
A growing body of evidence supports the impact of intermittent fasting on normalizing body metabolism and lowering oxidative stress and inflammation. Mounting evidence confirms that oxidative stress and chronic inflammation trigger the way for the development of metabolic diseases, such as diabetes. This research was conducted to evaluate the impact of Ramadan intermittent fasting (RIF) on the expression of cellular metabolism (SIRT1 and SIRT3) and antioxidant genes (TFAM, SOD2, and Nrf2). Fifty-six (34 males and 22 females) overweight and obese subjects and six healthy body weight controls were recruited and monitored before and after Ramadan. Results showed that the relative gene expressions in obese subjects in comparison to counterpart expressions of controls for the antioxidant genes (TFAM, SOD2, and Nrf2) were significantly increased at the end of Ramadan, with percent increments of 90.5%, 54.1% and 411.5% for the three genes, respectively. However, the metabolism-controlling gene (SIRT3) showed a highly significant (P < 0.001) downregulation accompanied with a trend for reduction in SIRT1 gene at the end of Ramadan month, with percent decrements of 61.8% and 10.4%, respectively. Binary regression analysis revealed significant positive correlation (P < 0.05) between high energy intake (>2000 Kcal/day vs. <2000 Kcal/day) and expressions of SOD2 and TFAM (r = 0.84 and r = 0.9, respectively). Results suggest that RIF ameliorates the genetic expression of antioxidant and anti-inflammatory, and metabolic regulatory genes. Thus, RIF presumably may entail a protective impact against oxidative stress and its adverse metabolic-related derangements in non-diabetic obese patients.